2021
DOI: 10.48550/arxiv.2106.01463
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lightweight Adapter Tuning for Multilingual Speech Translation

Hang Le,
Juan Pino,
Changhan Wang
et al.

Abstract: Adapter modules were recently introduced as an efficient alternative to fine-tuning in NLP. Adapter tuning consists in freezing pretrained parameters of a model and injecting lightweight modules between layers, resulting in the addition of only a small number of taskspecific trainable parameters. While adapter tuning was investigated for multilingual neural machine translation, this paper proposes a comprehensive analysis of adapters for multilingual speech translation (ST). Starting from different pre-trained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Moreover, Dong et al [1277] proposed a listen-understand-translate model, in which the proposed framework utilizes a pre-trained BERT model to enforce the upper encoder to produce as much semantic information as possible, without extra data. Le et al [1278] has presented a study of adapters for multilingual ST and shown that language-specific adapters can enable a fully trained multilingual ST model to be further specialized in each language pair.…”
Section: Pre-training With Unlabeled Speech/text Datamentioning
confidence: 99%
“…Moreover, Dong et al [1277] proposed a listen-understand-translate model, in which the proposed framework utilizes a pre-trained BERT model to enforce the upper encoder to produce as much semantic information as possible, without extra data. Le et al [1278] has presented a study of adapters for multilingual ST and shown that language-specific adapters can enable a fully trained multilingual ST model to be further specialized in each language pair.…”
Section: Pre-training With Unlabeled Speech/text Datamentioning
confidence: 99%
“…The development of multilingual models for either machine translation, speech translation or speech recognition often concern between versatility versus specialization [22]. The motivation comes from the disbelief that there are features being shared between languages and at the same time each language requires to selectively represented, and networks are encouraged to change "modes" depending on the language being processed [23].…”
Section: Language Adaptive Componentsmentioning
confidence: 99%
“…The motivation comes from the disbelief that there are features being shared between languages and at the same time each language requires to selectively represented, and networks are encouraged to change "modes" depending on the language being processed [23]. Since then, multingual model designers opt to use specific network components being presented for each language, ranging from weight generator [24] to adapters [15,22] or recently adaptive weights adding scales and biases to each weight matrix in the whole architecture [16]. In this paper, the last two options are selected for investigation thanks to being computationally manageable.…”
Section: Language Adaptive Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…We propose a music genre-conditioned training strategy to adapt an endto-end lyrics transcription system according to the music genre. Inspired by the success of adaptive fine-tuning with pre-trained models in natural language processing [19] and speech translation [20][21][22], we propose to incorporate genre-specific adapters to a pre-trained transformer-based polyphonic lyrics transcription model [23].…”
Section: Introductionmentioning
confidence: 99%